If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3(-16 + 4x) = -24 (-16 * 3 + 4x * 3) = -24 (-48 + 12x) = -24 Solving -48 + 12x = -24 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '48' to each side of the equation. -48 + 48 + 12x = -24 + 48 Combine like terms: -48 + 48 = 0 0 + 12x = -24 + 48 12x = -24 + 48 Combine like terms: -24 + 48 = 24 12x = 24 Divide each side by '12'. x = 2 Simplifying x = 2
| 6x+2=4x+16 | | 88-6x=39x+23x | | a^2-2a-8= | | -1-5z-7+12z=z+z+15+z+1 | | 5x+5=3x+35 | | 2/5g+2 | | -4/9n=8 | | y=37.4296+4.99 | | X-2(x-6)=-x+12 | | X/4+16=8 | | -8(6+5x)-3x=-5 | | x=7y+14 | | 3-2x/7=-5 | | 1/3y=1/4+5/12 | | 3/8n=12 | | 4x-3y=2.5 | | 3/10+3/17 | | ln((x+1)/(x-1)) | | 9(4x-3)+4(3x+7)= | | X/8+11=42 | | 15(y+2)=60 | | 3+2(x-1)=9x+4 | | 2x+2=-2(x+7) | | 200+0.15x=332 | | n+17=12 | | 8x+5=5x-7 | | 4x-4=4x-1-2 | | 6(3x+2)+5(4x+3)= | | 2x+3y=9.5 | | 5(x+7)=70 | | 108=473+23h | | 6-p2/8=-4 |